Deinococcus enclensis sp nov., isolated from a marine sediment sample - Thorat, Meghana N.; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S.; Dastager, Syed Gulam (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel pale-pink coloured strain, designated NIO-1023(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. The taxonomic position of strain NIO-1023(T) was investigated by using a polyphasic approach. The cells were observed to be Gram-stain positive, coccal shaped and non-spore forming. Phylogenetic analyses using the 16S rRNA gene sequence of the isolate indicated that the organism belongs to the genus Deinococcus. The strain NIO-1023(T) showed highest 16S rRNA gene sequence similarities with Deinococcus ficus (97.8 %), whereas other Deinococcus species showed less than 95 % sequence similarity. The DNA-DNA relatedness with respect to D. ficus CC-FR2-10(T) was 23.9 %. Chemotaxonomic data revealed that strain NIO-1023(T) contains only menaquinone MK-8 as the respiratory quinone and a complex polar lipid profile consisting of different unidentified glycolipids and polar lipids, two unknown phospholipids and three unknown phosphoglycolipids. As in other deinococci, one of these phosphoglycolipids was predominant in the profile. The predominant fatty acids were identified as C-17:1 w8c, C-16:1 w6c/w7c, C-15:1 w6c and C-17:1 w9c. The genomic DNA G + C content of strain NIO-1023(T) was determined to be 67.2 mol%. The biochemical and chemotaxonomic properties demonstrate that strain NIO-1023(T) represents a novel species, for which the name Deinococcus enclensis sp. nov. is proposed. The type strain is NIO-1023(T) (=DSM 25127(T) = NCIM 5456(T)).
Keywords: 16S rRNA; Deinococcus; Marine sediments; Polyphasic

Exiguobacterium enclense sp nov., isolated from sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Thorat, Meghana N.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive bacterium, designated strain NIO-1109(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. Phenotypic and chemotaxonomic characteristics and data from phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1109(T) was related to the genus Exiguobacterium. Strain NIO-1109(T) exhibited >98.0% 16S rRNA gene sequence similarity with respect to Exiguobacterium indicum HHS 31(T) (99.5%) and Exiguobacterium acetylicum NCIMB 9889(T) (99.1 %); the type strains of other species showed <98% similarity. Levels of DNA DNA relatedness between strain NIO-1109(T) and E. acetylicum DSM 20416(T) and E indicum LMG 23471(T) were less than 70% (33.0 +/- 2.0 and 37 +/- 32%, respectively). Strain NIO-1109(T) also differed from these two closely related species in a number of phenotypic traits. Based on phenotypic, chemotaxonomic and phylogenetic data, strain NIO-1109(T) is considered to represent a novel species of the genus Exiguobacterium, for which the name Exiguobacterium enclense sp. nov. is proposed. The type strain is NIO-1109(T) (=NCIM 5457(T)= DSM 25128(T)=CCTCC AB 2011124(T)).

Microbacterium enclense sp nov., isolated from sediment sample - Mawlankar, Rahul R.; Mual, Poonam; Sonalkar, Vidya V.; Thorat, Meghana N.; Verma, Ashish; Srinivasan, Krishnamurthi; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel bacterium (strain NIO-1002(T)) belonging to the genus Microbacterium was isolated from a marine sediment sample in Chorao Island, Goa Province, India. Its morphology, physiology, biochemical features and 16S rRNA gene sequence were characterized. Cells of this strain were Gram-stain-positive, non-motile, non-spore-forming rods that formed yellow-pigmented colonies. It grew in 0-12 % (w/v) NaCl and at 25-37 degrees C, with optimal growth at 30 degrees C. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1002(T) is associated with members of the genus Microbacterium, with highest sequence similarity with Microbacterium hominis CIP 105731(T) (98.1%) and Microbacterium testaceum KCTC 9103(T) (98.0 %). Within the phylogenetic tree, this novel strain shared a branching point with M. hominis CIP 105731(T). The DNA G+C content was 66.5 mol% and DNA DNA hybridization relatedness between NI-1002(T), M. hominis CIP 105731(T) and M. testaceum KCTC 9103(T) was 39.0 +/- 2.0 % and 41.0 +/- 2.0 %, respectively. The major fatty acids were ai-C-15:0, i-C-16:0 and al-C-17:0 and the diamino acid in the cell-wall peptidoglycan of NIO-1002(T) was lysine. Data obtained from DNA-DNA hybridization and chemotaxonomic phenotypic analysis support the conclusion that strain NIO-1002(T) represents a novel species within the genus Microbacterium. The name Microbacterium enclense sp. nov. is proposed, with NIO-1002(T) (=NCIM 5454(T)=DSM 25125(T)=CCTCC AB 2011120(T)) as the type strain.

Bacillus cellulasensis sp nov., isolated from marine sediment - Mawlankar, Rahul R.; Thorat, Meghana N.; Krishnamurthi, Srinivasan; Dastager, Syed Gulam (Archives of Microbiology, 2016)
A novel bacterial strain NIO-1130(T) was isolated from sediment sample taken from Chorao Island, Goa Province, India, and subjected to a taxonomic investigation. The strain was Gram-positive, aerobic, and motile. Phylogenetic analysis based on 16S rRNA gene sequences placed the isolate within the genus Bacillus and strain NIO-1130(T) showed highest sequence similarity with Bacillus halosaccharovorans DSM 25387(T) (98.4 %) and Bacillus niabensis CIP 109816(T) (98.1 %), whereas other Bacillus species showed < 97.0 % similarity. Tree based on gyrB gene sequence revealed that strain bacillus group. The major menaquinone was MK-7 and the predominant cellular fatty acids were iso-C-15:0, anteiso-C-15:0, iso-C-17:0, and anteiso-C-17:0. The strain showed a DNA G+C content of 39.9 mol%. DNA-DNA hybridization studies revealed that strain NIO-1130(T) exhibits 70 % similarity with Bacillus halosaccharovorans DSM 25387(T) and Bacillus niabensis CIP 109816T. On the basis of physiological, biochemical, chemotaxonomic and phylogenetic analyses, we consider the isolate to represent a novel species of the genus Bacillus, for which the name Bacillus cellulasensis sp. nov., is proposed. The type strain is NIO-1130(T) (=NCIM 5461(T) = CCTCC AB 2011126(T)).
Keywords: Bacillus sp; Cellulase; Marine sediment; Polyphasic taxonomy

Microbacterium enclense sp. nov., isolated from sediment sample (vol 65, pg 2064, 2015) - Mawlankar, Rahul R.; Mual, Poonam; Sonalkar, Vidya V.; Thorat, Meghana N.; Verma, Ashish; Srinivasan, Krishnamurthi; Dastager, Syed G. (International Journal of Systematic and Evolutionary Microbiology, 2019)

New TBAF complex, highly stable, facile and selective source for nucleophilic fluorination: applications in batch and flow chemistry - Said, Madhukar S.; Khonde, Nilesh S.; Thorat, Meghana N.; Atapalkar, Ranjit S.; Kulkarni, Amol A.; Gajbhiye, Jayant; Dastager, Syed G. (Asian Journal of Organic Chemistry, 2020)
Natural polysaccharides supported tetrabutylammonium fluoride (TBAF) complexes are prepared and found to be highly stable and selective fluoride source for well-renowned nucleophilic (SN2 type) fluorination reactions for the first time. Bacterial cellulose, plant cellulose, pectin, and starch derived TBAF complexes are synthesized, characterized (using SEM, TEM, and NMR techniques) and studied for their stability and reactivity. Heterogeneous bacterial cellulose-TBAF complex (NBu4(Bac-cell-OH)F) 1 was found to be highly stable and non-hygroscopic among all complexes, which gave high yields of fluorinated products in multi-gram scale in shorter reaction time. The primarily developed batch protocol was extended to solid-solid continuous flow reaction using an in-house built screw reactor, which furnished products in a few seconds of residence time (tR=20-25 sec) and excellent yields.
Keywords: Flow synthesis; fluorination; green chemistry; Sustainable Chemistry

Fabrication of bacterial nanocellulose/polyethyleneimine (PEI-BC) based cationic adsorbent for efficient removal of anionic dyes - Thorat, Meghana N.; Jagtap, Ashish; Dastager, Syed G. (Journal of Polymer Research, 2021)
A bacterial cellulose (BC) based adsorbent was prepared by using polyethyleneimine (PEI) using epichlorohydrin as a cross-linker. The physicochemical characterization of the of the developed adsorbent was carried out using FTIR, BET analysis and SEM, respectively. The dye removal efficiency of the adsorbent was assessed towards two anionic model dyes viz. congo red (CR) and reactive red 120(RR). The kinetic data for the removal of both the anionic dyes were fitted better using pseudo-second-order model. Langmuir model describes well the process of adsorption with predicted maximum adsorption capacity (q(max)) 515.46 and 300.3 mg L-1 for CR (at pH 6.0) and RR (at pH 3.0) respectively. The adsorption-desorption study showed that PEI-BC adsorbent is effective with more than 90% dye removal efficiency even after four cycles. Furthermore, the bactericidal activity of the adsorbent was analysed using Escherichia coli and Staphylococcus aureus and adsorbent showed good inhibition against both test organisms. The study reveals that PEI-BC adsorbent can be a good candidate for water remediation purpose bearing multifunctional behaviour.
Keywords: adsorbent; Anionic dyes; Bacterial cellulose; Bactericidal; Polyethyleneimine